Evaluation of clinical tests and magnetic resonance imaging for knee meniscal injuries: correlation with video arthroscopy() - Antunes, Leonardo Côrtes (Rev Bras Ortop, 2017)
OBJECTIVE: To determine the specificity, sensitivity, accuracy, likelihood, and correlation of the findings of meniscal tests and magnetic resonance imaging (MRI) to knee video arthroscopy. METHODS: A cross-sectional study, conducted between June and December 2015, which evaluated 84 patients with meniscal tears (MT) selected for video arthroscopy. Two orthopedic trainees and a resident performed a physical examination with specific tests. The results and reports from MRI were compared with arthroscopy findings. The data were analyzed in the statistical program R. RESULTS: The Steinmann I test was the most specific, with specificity of 86% and 91% for medial meniscus tears (MMT) and lateral meniscus tears (LMT), respectively. With regard to accuracy, the pain test on palpation of the joint interline (PPJI) showed values of 67% and 73% for detection of MMT and LMT, respectively. The PPJI test showed higher sensitivity, with a 77% chance of detecting MMT. Analysis of the set of three tests (McMurray, PPJI, and Steinmann I) compared to arthroscopy showed 85% sensitivity for MMT and 70% sensitivity for LMT. MRI showed a greater specificity for the diagnosis of MMT and LMT; the values were 82% and 91%, respectively. CONCLUSION: The combination of the three tests shows better results compared to the isolated tests and thus can be associated to the MRI to make an effective diagnosis. However, further studies assisting in the development of a protocol to standardize diagnostic evaluation are required.